Maternal and neonatal outcomes in late preterm prelabour rupture of membranes: a retrospective study - Leelodharry, Vakil Kumar (Department of Obstetrics and Gynaecology, 2019)
Background: The management of late preterm prelabour rupture of membranes (PPROM) is associated with an increased risk of neonatal prematurity related morbidity due to many obstetric care guidelines which favour delivery at 34 weeks or immediately upon diagnosis of ruptured membranes after 34 weeks gestation. However, expectant management of this group of patients (i.e delayed delivery) between 34+0 and 36+6 weeks of gestation is associated with an increased risk of neonatal and maternal infectious morbidities. Aim of Study: The aim of this study was to evaluate the impact of the latency period on maternal and neonatal outcomes in late preterm prelabour rupture of membranes in a regional perinatal service in Cape Town, South Africa. The latency period was defined as the time from rupture of membranes to the time of delivery. In addition, we sought to investigate whether immediate induction of labour in the absence of overt signs of infection or fetal compromise should be prioritised in women who present with late preterm prelabour rupture of membranes. Methods: This was a retrospective cohort study carried out over a period of two years in two secondary level hospitals of the Metro West area of Cape Town. The subjects were low risk HIV negative women with singleton pregnancies with ruptured membranes in the late preterm period. Maternal and neonatal outcomes were studied between two latency periods, namely short latency (< 48 hours) and long latency period (≥ 48 hours) after ruptured membranes. Results and Conclusion: There were no significant differences in maternal and neonatal outcomes between the two groups of latency periods when latency was defined as the time from ruptured membranes to delivery. The study favoured a delayed induction thereby improving neonatal outcomes by decreasing the complications of prematurity. There were more adverse maternal outcomes, including an increase likelihood of augmentation of labour and more operative delivery along with its major risk, that of obstetric haemorrhage, were noted in the short latency period group. Therefore, a delayed induction policy appeared to be more appropriate. Preterm delivery places the newborn at risk of prematurity. Therefore, the risk of prematurity must be balanced with the risks of intrauterine infection and antepartum haemorrhage, the two major complications of expectant management if delayed induction is to be adopted. Proper monitoring of both the pregnant woman and fetus is essential when expectant management is carried out to avoid these adverse maternal and neonatal outcomes.